2019
DOI: 10.1101/851618
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Axon-dependent expression of YAP/TAZ mediates Schwann cell remyelination but not proliferation after nerve injury

Abstract: 1 2 YAP and TAZ are transcriptional regulators that powerfully stimulate cell proliferation, which 3 drives developmental or tumorigenic tissue growth. Previously we showed that YAP/TAZ 4 initiate and maintain Schwann cell (SC) differentiation, thereby forming and maintaining myelin 5 sheath around peripheral axons (Grove et al., 2017). Here we show that YAP/TAZ are required 6 for SCs to restore peripheral myelination after nerve injury. We find that YAP/TAZ dramatically 7 disappear from denervated, proliferat… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 49 publications
2
8
0
Order By: Relevance
“…These results confirm the important role of YAP and TAZ during remyelination observed in a recent study using the complete ablation of Yap and Taz (Grove et al, 2020); validating the use of the compound model Yap cHet ; Taz cKO to investigate the long‐term function of YAP and TAZ in remyelination. Since one copy of Yap is not enough to compensate for the lack of Taz , this suggests that similar to its role during SC development (Deng et al, 2017; Grove et al, 2017; Poitelon et al, 2016), Taz has a more prominent role in nerve repair compare to Yap (Grove et al, 2020). Finally, these data show that loss of YAP and TAZ expression, at least up to 60 dpi, induces a severe remyelination defect but does not constitute a complete block in peripheral nerve regeneration process.…”
Section: Resultssupporting
confidence: 89%
See 4 more Smart Citations
“…These results confirm the important role of YAP and TAZ during remyelination observed in a recent study using the complete ablation of Yap and Taz (Grove et al, 2020); validating the use of the compound model Yap cHet ; Taz cKO to investigate the long‐term function of YAP and TAZ in remyelination. Since one copy of Yap is not enough to compensate for the lack of Taz , this suggests that similar to its role during SC development (Deng et al, 2017; Grove et al, 2017; Poitelon et al, 2016), Taz has a more prominent role in nerve repair compare to Yap (Grove et al, 2020). Finally, these data show that loss of YAP and TAZ expression, at least up to 60 dpi, induces a severe remyelination defect but does not constitute a complete block in peripheral nerve regeneration process.…”
Section: Resultssupporting
confidence: 89%
“…Others and we showed that SCs lacking both YAP and TAZ are unable to proliferate properly and fail to myelinate developing peripheral nerves (Deng et al, 2017; Grove et al, 2017; Poitelon et al, 2016). Grove et al recently reported that YAP and TAZ are also essential for functional regeneration of peripheral nerves using inducible Yap and Taz double knockout in SC; Yap fl/fl; Taz fl/fl; Plp1 ‐cre ER (Grove et al, 2020). However, animals ablated for both Yap and Taz in adult myelinating SCs and oligodendrocytes exhibit severe weight loss, tremors, ataxia, and mortality within 2 weeks (Figure S1) (Deng et al, 2017; Grove et al, 2017), which prevents the assessment of the long‐term effect of YAP and TAZ loss required to make conclusions on their role in myelin maintenance and nerve regeneration after injury.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations